К вопросу об определении клише - Драздаускене, Мария-Людвика (Kalbotyra, 1988)
The article deals with the question of the definition of the cliché as contrasted with the stereotypical unit. The cliché is considered to be a functional unit of language entering a set of fixed global units (forms of address, formulae, response utterances and stereotypical units) recurrent in the phatic use of English. Thus the question is treated as a subject of stylistic contextology rather than phraseology. Considering its semantic properties, the cliché is defined as a fixed idiomatic global unit characterized by a hackneyed evaluative meaning arising from its fossilized qualifying and nominal components as well as from its potential meaning of sociocultural nature. The stereotypical unit is defined as a fixed non-idiomatic global unit devoid of evaluative meaning because of its variable qualifying, nominal and verbal components as well as of its potential meaning of sociolinguistic nature. Given identical frequency. the cliché is objectionable in usage because of its hackneyed evaluative meaning, whilst the stereotypical unit is common in usage because it is free of hackneyed evaluation.